Anacardium occidentale L. Leaf extracts protect against glutamate/H2O2-induced oxidative toxicity and induce neurite outgrowth: the involvement of SIRT1/Nrf2 signaling pathway and teneurin 4 transmembrane protein - Duangjan, Chatrawee; Rangsinth, Panthakarn; Zhang, Shaoxiong; Wink, Michael; Tencomnao, Tewin (Frontiers in pharmacology, 2021)
Neurodegenerative diseases are linked to neuronal cell death and neurite outgrowth impairment that are often caused by oxidative stress. Natural products, which have neuroprotective against oxidative stress and neurite outgrowth inducing activity, could be potential candidates for alternative treatment of neurodegenerative diseases. This study aims to investigate the effects of Anacardium occidentale leaf extracts on neuroprotective and neuritogenesis properties in cultured neuronal (HT22 and Neuro-2a) cells. We found that gallic acid, catechin and quercetin were the main compounds in A. occidentale extracts. The extracts have a protective effect against glutamate/H2O2-mediated oxidative stress-induced cell toxicity. The gene expression of cellular antioxidant enzymes (SODs, GPx and, GSTs) were up-regulated by this treatment. The treatment also triggered SIRT, Nrf2 proteins as well as the mRNA transcriptions of relevant anti-oxidation genes (NQO1, GCLM, and EAAT3). We demonstrated that the extracts promote antioxidant defense in neuronal cells via the SIRT1/Nrf2 signaling pathway. Moreover, the extracts increase neurite outgrowth and Ten-4 expression in Neuro-2a cells. However, the neuritogenesis properties did not occur, when Ten-4 expression was knocked down by corresponding siRNA. These results suggest that the leaf extracts have an interesting neuritogenesis and neuroprotective potential against glutamate/H2O2-mediated toxicity and could be a potential therapeutic candidate for neurodegenerative diseases.
Im Text ist "2" jeweils tiefgestellt
Gesehen am 28.07.2021